On the theorems of A. Khintchine and J. Kubilius - Sprindzuk, V. G. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Г. Спринджук, О теоремах А. Я. Хинчина и И. П. Кубилюса V. Sprindžiuk, Apie A. Chinčino ir J. Kubiliaus teoremas